Willingness to Pay for the National Health Insurance Scheme: A Cross-sectional study in Sarawak, Malaysia (Bangladesh Journal of Medical Science, 2022)
Introduction: Globally, the cost of healthcare continues to rise due to demographic changes of the ageing population, the rise of non-communicable diseases (NCD) prevalence, advances in medical technologies, and innovations. Malaysia is also not an exception, where the total health expenditure has risen from MYR 8.55 billion to MYR 57.36 from 1997 to 2017. With the ongoing debate on the tax-based public healthcare system’s long-term sustainability, several scholars have called to introduce national health insurance in the country. The current study has contributed to the understanding of willingness to pay (WTP) among the Malaysian population. However, there is a gap of knowledge regarding WTP in the rural area of Sarawak.Methods: A cross-sectional study was conducted in rural areas of Sarawak involving 45 villages from 6 rural districts that represent the North, Central and Southern regions. Through an interviewer-administered questionnaire, the instrument consisted of demographic profile, presence of underlying disease, social capital, wealth index, and willingness to pay for national health insurance scheme (NHIS) through iterative bidding method of CVM. Three regression analysis (binary logistic, multinomial logistic, negative binomial logistic) were computed to identify statistically significant factors across these three analyses.Results: The total number of respondents was 1208. The amount that participants willing to pay for NHIS was higher. However, the proportion of participants willing to participate was lower when compared to similar previous studies. On an average, the respondents were willing to pay MYR 40.84 (SD 35.36) per month for NHIS premium. Factors favouring their willingness to pay were smaller family size, presence of underlying diseases, a strong level of empowerment, weaker group and network connection, low social cohesion and inclusion, and finally, low perception of violence and conflicts. These were identified as factors that were found to be significant across three statistical analyses.Conclusion: Hence, the government needs to consider the differences in terms of geographical location (Peninsular, Sabah and Sarawak) and socio-demographic characteristics when considering the deployment of NHIS nationwide. Furthermore, communication with the local communities, organisation and group is very important to improve rural communities’ participation. Steps have to be taken to avoid adverse selection, considering that ill individuals were more likely willing to join thana healthier person.Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 577-589